الذكاء الروحي وعلاقته بكل من اليقظة العقلية والابتكارية الانفعالية لدى عينة من معلمي التربية الخاصة بمحافظة المنيا - أحمد، مصطفى علي نمر علي Ahmed, Mustafa Ali Nemr Ali (جامعة الوادي الجديد - كلية الآداب, 2021)
هدفت الدراسة الحالية إلى الكشف عن طبيعة العلاقة بين الذكاء الروحي وكل من اليقظة العقلية والابتكارية الانفعالية لدى معلمي التربية الخاصة بمحافظة المنيا، وكذلك معرفة الفروق في متغيرات الدراسة تبعا للعمر والنوع وسنوات الخبر، ومن جهة أخري هدفت إلى معرفة مدي إسهام كل من اليقظة العقلية والابتكارية الانفعالية في التنبؤ بالذكاء الروحي، وتكونت عينة الدراسة من ٣٧٢ معلم ومعلمه (194 ذكور- 178 إناث) بمدراس التربية الخاصة وهى مدرسة الأمل للصم وضعاف السمع بديرمواس، ملوي، منشاة الفكرية بأبو قرقاص والمنيا، إطسا بسمالوط، ومغاغة التابعين لمحافظة المنيا، وقام الباحث بتطبيق مقياس الذكاء الروحي، مقياس اليقظة العقلية ومقياس الابتكارية الانفعالية، واستبانة جمع المعلومات الديموغرافية، وتوصلت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية بين أفراد العينة تبعا لمتغير النوع على مقاييس الدراسة في صالح الذكور، في حين وجدت فروق تبعا للعمر في الذكاء الروحي في صالح الأعلى عمرا، في حين لم توجد فروق ذات دلالة إحصائية تبعا للعمر في أدائهم على مقاييس اليقظة العقلية والابتكارية الانفعالية، كما وجدت فروق دالة إحصائيا وفقا لمستوى سنوات الخبرة في صالح الأعلى خبرة في أدائهم على مقاييس الذكاء الروحي واليقظة العقلية، في حين لم توجد فروقا بينهم في الابتكارية الانفعالية، وقد أظهرت النتائج وجود علاقة ارتباطية إيجابية بين الذكاء الروحي وكل من اليقظة العقلية والابتكارية الانفعالية لدى معلمي مدارس التربية الخاصة؛ وأظهرت، النتائج الخاصة بالإسهام أو التنبؤ في الذكاء الروحي لدى أفراد العينة إلى أن المتغيرات المستقلة المتمثلة في اليقظة العقلية والابتكارية الانفعالية تؤثر إيجابيا وتسهم بنسبة كبيرة. The current study aimed to reveal the nature of the relationship between spiritual intelligence and both mindfulness and emotional creativity among special education teachers, as well as knowing the differences in the study er and years of experience, variables according to age, gendand on the other hand, it aimed to know the extent to which both mindfulness and emotional creativity contributed to prediction. With spiritual intelligence, the study sample 874 -males 848 male and female teachers ( 273 consisted of Amal -females) in special education schools, which are AlSchool for the Deaf and Hard of Hearing in Dermwas, Fikariah in Abu Qurqas and Minya, -Mallawi, Manshaat AlAtsa in Samalout, and Maghagha belonging to Minya creativity scale, and Governorate. mindfulness, emotional demographic information collection questionnaire. The results of the study concluded that there were statistically significant differences between the sample members according to the es, while gender variable on the study scales in favor of malthere were differences according to age in spiritual intelligence in favor of the oldest, while no There are statistically significant differences according to age in their performance on the measures of mindfulness and emotional ell as statistically significant differences creativity, as waccording to the level of their age. The experience was in favor of the most experienced in their performance on the measures of spiritual intelligence and mindfulness, while em in emotional there were no differences between thcreativity. The results showed a positive correlation between spiritual intelligence and both mindfulness and emotional The creativity among teachers of special education schools. ence results of contributing or predicting the spiritual intelligof special education teachers showed that the independent variables represented in mindfulness and emotional creativity have a positive impact and contribute to a large percentage.
Keywords: علم النفس التربوى -- العملية التعليمية -- المهارات الشخصية -- اليقظة الذهنية -- معلمو المدارس -- مصر